Postcolonial Female Intellectual Agency: Siti Baroroh Baried and the Making of Arabic Philological Scholarship at Universitas Gadjah Mada (1946–1963) - Ruliah Sari; Nur Aini Setiawati (Diakronika, 2025)
This study highlights the significant role of Siti Baroroh Baried in the intellectual transformation of post-colonial higher education at Universitas Gadjah Mada (UGM) between 1946 and 1963. It aims to analyze and reconstruct her scholarly contributions to the development of philological studies, as well as her pioneering role in establishing the Department of Arabic Literature at UGM. Her work reflected a broader shift in post-colonial academic thought through her influence on academic discourse, institutional practices, and women’s participation in intellectual life at UGM. The method used in this research is the historical method, encompassing heuristics, source criticism, interpretation, and historiography. The result shows the strong ethical and intellectual foundation in Siti Baroroh Baried stemmed from her family background in the Kauman, Yogyakarta, which highly upheld religious values and education. Beginning in 1946, she received significant support from several progressive-minded UGM lecturers. This support created a more inclusive and egalitarian intellectual environment, enabling the active participation of women without being limited by gender stereotypes. Through her scholarly work and teaching practices, Baried contributed to the advancement of philological studies by introducing systematic approaches to Arabic texts, developing early instructional materials, and institutionalizing Arabic literary studies at Universitas Gadjah Mada in 1962. This study argues that Siti Baroroh Baried represents a form of post-colonial female intellectualism, manifested through her academic leadership, institutional role, and lasting contributions to Arabic literary studies at Universitas Gadjah Mada.